Phytochemical investigation of methanolic extract of Zataria multiflora Boiss. - Emad Nazaryanpour; Samad Nejad Ebrahimi (Institue of Medicinal Plants, ACECR, 2020)
Background: Zataria multiflora Boiss. (Lamiaceae) has been found in Iran, Afghanistan, and Pakistan. Z. multiflora called 'Avishane Shirazi' in Persian is used as a seasoned in many foods in Iran. The literature survey demonstrated that Z. multiflora has immunostimulant, pain-relieving, antinociceptive, anti-inflammatory, antioxidant, antibacterial, antiviral, antiparasitic, antifungal effects and also widely used in traditional medicine for analgesia, diarrhea, infectious diseases, and gastrointestinal problems. Objective: The subject of this study is performing phytochemical constituents of methanolic extract of Z. multiflora. Methods: The application of various chromatographic techniques such as normal and reverse C18 chromatography let to isolation, purification and identification of several flavonoids. Results: In this investigation, the fractionation of methanol extract of the aerial parts of Z. multiflora led to the isolation and purification of three known flavonoid glycosides namely Luteolin 7-O-glucopyranoside, Apigenin 7-O-rutinoside and Luteolin 7-O-rutinoside whose structures were determined by 1D and 2D-NMR spectroscopic studies, in particular, homo-COSY and hetero (HSQC and HMBC). Conclusion: The results show a methanolic extract of Z. multiflora is a rich source of flavonoids and triterpenoids.